2007
DOI: 10.1146/annurev.biophys.36.040306.132705
|View full text |Cite
|
Sign up to set email alerts
|

Living with Noisy Genes: How Cells Function Reliably with Inherent Variability in Gene Expression

Abstract: Within a population of genetically identical cells there can be significant variation, or noise, in gene expression. Yet even with this inherent variability, cells function reliably. This review focuses on our understanding of noise at the level of both single genes and genetic regulatory networks, emphasizing comparisons between theoretical models and experimental results whenever possible. To highlight the importance of noise, we particularly emphasize examples in which a stochastic description of gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
273
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(283 citation statements)
references
References 70 publications
8
273
0
2
Order By: Relevance
“…Noise within genetic circuits is typically known to destabilize stable states (48,49). Numerous studies have demonstrated that noise can provide the perturbation for a system to escape the attraction of stable states and trigger switching between distinct phenotypes (48,50,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noise within genetic circuits is typically known to destabilize stable states (48,49). Numerous studies have demonstrated that noise can provide the perturbation for a system to escape the attraction of stable states and trigger switching between distinct phenotypes (48,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that noise can provide the perturbation for a system to escape the attraction of stable states and trigger switching between distinct phenotypes (48,50,51). For example, the phage-lysis-lysogeny cellular decision-making switch was one of the first systems for which noise was proposed to be the trigger (52).…”
Section: Discussionmentioning
confidence: 99%
“…Fluctuations in the process of transcription can generate considerable cell-to-cell variability in the expression level of genes across isogenic cell populations (Blake et al 2003;Kaern et al 2005;Maheshri and O'Shea 2007;Raj and van Oudenaarden 2009). This variability can result in phenotypic diversity and thus lead to potentially important effects on many cellular and developmental processes.…”
mentioning
confidence: 99%
“…Specifically, we show when entrainment of the population to a reference sinusoidal signal is possible in open and closed loop control and whether the spatially resolved population can track a time-varying reference signal. Since we use an ABM approach we also study the effect of cell-to-cell heterogeneity across the population, as in a physical setting cell dynamics will tend to vary slightly even between members of the same colony [2, 30,31]. Hence, the model serves as an in silico test-bed where cellular populations are simulated in a spatially explicit 3D-environment and the ability to entrain each population using open and closed loop methods is compared.…”
Section: Introductionmentioning
confidence: 99%